Political empowerment of women - Narain, Yogendra; Lakshmi, L.; Sahu, S.N. (2005)
There still exists a wide gap between the enunciated goals and situational reality of status of women in India. The need for strengthening the legal systems aimed at elimination of all forms of discrimination has been emphasised time and again. The first five Five-Year Plans viewed the issue of women and their development from the welfare point of view. The later Plans took this issue with a strategy for their empowerment. Yet, in spite of a broad framework and perspective for women's empowerment, it is imperative that these initiatives and strategies are translated into social, political, economic, educational and cultural empowerment of women. - Reproduced.
Keywords: Women in politics - India; Women in politics